2020
DOI: 10.1080/15548627.2020.1833515
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin prevents spontaneous abortion by triggering decidual stromal cell autophagy-mediated NK cell residence

Abstract: Deficiency in decidualization has been widely regarded as an important cause of spontaneous abortion. Generalized decidualization also includes massive infiltration and enrichment of NK cells. However, the underlying mechanism of decidual NK (dNK) cell residence remains largely unknown. Here, we observe that the increased macroautophagy/autophagy of decidual stromal cells (DSCs) during decidualization, facilitates the adhesion and retention of dNK cells during normal pregnancy. Mechanistically, this process is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 50 publications
(54 reference statements)
2
71
0
Order By: Relevance
“…It has been described that autophagy is highly activated in decidualized endometrium of early pregnancy, which increases NK cell adhesion and retention in the decidua. Also, when autophagy is inhibited, decidual NK (dNK) cell residence is decreased, contributing to spontaneous abortion (171). Tan et al described that autophagy levels are highly reduced in cases of recurrent miscarriage.…”
Section: Role Of Autophagy In Placental and Cancer Immune Evasionmentioning
confidence: 99%
“…It has been described that autophagy is highly activated in decidualized endometrium of early pregnancy, which increases NK cell adhesion and retention in the decidua. Also, when autophagy is inhibited, decidual NK (dNK) cell residence is decreased, contributing to spontaneous abortion (171). Tan et al described that autophagy levels are highly reduced in cases of recurrent miscarriage.…”
Section: Role Of Autophagy In Placental and Cancer Immune Evasionmentioning
confidence: 99%
“…Autophagy is hormonally regulated in the endometrium and plays essential roles in physiological and pathological processes [ 55 ]. Additionally, autophagy is involved in energetic metabolism via recycling metabolites to promote the survival of EECs and trophoblasts under low oxygen and low nutrient conditions of the maternal–fetal interface [ 56 ]. Toschi et al reported that the autophagy pathway is required for vasculogensis and placental development during early pregnancy in sheep [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics of uNK cells are likely to prevent microbial infections 77 . Our recent studies demonstrated that the increase of autophagy of ESCs should promote the residence of NK cells in endometrium/decidua through upregulating MMP-9 and adhesion molecules expression 87 . Therefore, the increased numbers of resident uNK cell in the endometrium, triggered by high levels of autophagy during menstruation, supports immune defense.…”
Section: The Estrogen / Progesterone-autophagy-immunity Axis In Menstmentioning
confidence: 98%
“…In addition, autophagy induces G0/G1 arrest and apoptosis in menstrual blood-derived endometrial stem cells 97 . Autophagy of ESC promotes the upregulation of MMP9 in a melanocyte inducing transcription factor (MITF)- herpesvirus entry mediator (HVEM)-dependent manner 87 , resulting in rapid ECM degradation and endometrial exfoliation occur during menstruation. Remarkably, the intracellular composition of the ESC can be renewed through autophagy.…”
Section: The Estrogen / Progesterone-autophagy-immunity Axis In Menstmentioning
confidence: 99%
See 1 more Smart Citation